PERANCANGAN INSTRUMEN PENILAIAN KESIAPSIAGAAN PUSKESMAS DALAM PENANGGULANGAN BENCANA - Cut Dian; Imran .; Khairul Munadi (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Primary health care center preparedness in disaster management is very important to reduce the impact of disasters occurring in the community. It is necessary to assess the level of Primary health care center preparedness in disaster management to know the level of preparedness and the aspects of preparedness that need to be improved. No instruments have been used to assess Primary health care preparedness in disaster management. This study aims to identify indicators of preparedness of Primary health care center in disaster management, to design the instrument of Primary health care center preparedness assessment in disaster management. This research specifically uses Research and Development research. Outline consists a) Introduction Research, b) Planning and Design of instrument, c) weighting, d) Professional judgment e) Validity test instrument using Content Validity Ratio (CVR). This study has identified six indicators of Primary health care center preparedness that are health mapping, daily emergency services, community empowerment, preparedness exercises, surveillance and cross sector coordination. This research has produced the instrument that has been tested its validity, to assess the preparedness of Primary health care in disaster response. Keywords: assessment instruments, preparedness, primary health care center, disaster management